PERBANDINGAN KINERJA DAN EFISIENSI STRUKTUR PENAHAN GEMPA SRPM DAN SISTEM GANDA SRPM DENGAN DINDING GESER (SHEAR WALL) DENGAN METODE PUSHOVER - Muhammad Affan Ghaffar; Bantot Sutriono; Masca Indra Triana (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
In planning a building structure the main aspects that must be considered are strength and efficiency, which in designing the structure must be designed as efficient as possible but its strength is guaranteed. To design reinforced concrete building structures, it is regulated in SNI-2847-2019. Because Indonesia is a country with high seismic activity, in planning high-rise building structures, it must also be designed to be earthquake-resistant according to SNI-1726-2019 regulations. In this study a comparison of the SRPM earthquake retaining structure and the SRPM Dual System with shear wall will be carried out to determine the comparison of performance and efficiency. The results of the analysis in this study show that the maximum drift story value of the SRPM structure in the X direction is 55.655 and the Y direction is 61.171, while for the Dual System structure the X direction is 42.191 and the Y direction is 44.495. The results of the structure performance level analysis with using the pushover analysis method based on REMA 440 of the SRPM and Dual System structures can be categorized under IO conditions (Immadiate Occupancy). For efficiency comparison result the SRPM structure has a reinforcement weight of 263,729.72 kg and a concrete volume of 1643.4 m3, while the Double Site structure has a reinforcement weight of 214,731.38 kg and a concrete volume of 1300.6 m3.